2016
DOI: 10.1111/jcpt.12485
|View full text |Cite
|
Sign up to set email alerts
|

Clinical analysis of hyperkalemic renal tubular acidosis caused by calcineurin inhibitors in solid organ transplant recipients

Abstract: We should alert for CNI-induced hyperkalemic RTA in transplant recipients. By CNI dosage reduction or adding low dose fludrocortisone, or temporarily switching to SRL, the prognosis of CNI-induced hyperkalemic RTA is favourable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…1b). All patients were on tacrolimus, which is the most likely causative agent in keeping with previous studies, which have reported type-4 RTA in patients on tacrolimus following solid organ transplants [18][19][20]. An observational study involving 106 transplant patients on CNIs reported the prevalence of type-4 RTA to be 30.9%.…”
Section: Discussionsupporting
confidence: 66%
“…1b). All patients were on tacrolimus, which is the most likely causative agent in keeping with previous studies, which have reported type-4 RTA in patients on tacrolimus following solid organ transplants [18][19][20]. An observational study involving 106 transplant patients on CNIs reported the prevalence of type-4 RTA to be 30.9%.…”
Section: Discussionsupporting
confidence: 66%
“…There remains an ongoing debate regarding the development of tubulopathies post‐renal transplantation with perhaps under recognition in clinical practice. Acute nephrotoxic injuries certainly contribute in many cases; however, CNI‐based immunosuppressive regimens are certainly recognized to cause tubular dysfunction . Renal transplant patients treated with CNIs such as ciclosporin A and tacrolimus (FK 506) may develop signs of partial resistance to aldosterone action with subsequent hyperkalaemia and metabolic acidosis, thus partially explaining the mechanism of action of fludrocortisone in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…However, the incidence of this type 4 renal tubular acidosis remains unknown. Whilst tubular dysfunction can occur secondary to renal impairment and interstitial damage from acute episodes and nephrotoxic drugs, immunosuppressive regimens namely CNI (ciclosporin, tacrolimus) have also been directly implicated . These drugs are thought to lead to a down regulation of the mineralocorticoid receptors and a resultant pseudohypoaldosteronism picture with normal aldosterone levels.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon has only been described in rare cases following liver transplantation [57]. Patients with type IV RTA tend to be asymptomatic with normal creatinine and urine output.…”
Section: Discussionmentioning
confidence: 99%